2016
DOI: 10.5539/apr.v8n4p92
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Attenuation and Reduction of Backscattered Radiation

Abstract: This paper reports the comparative study of X-ray attenuation using different materials which can be utilized to design anti-backscattered grids and radiation protection shields. The characteristics of X-ray attenuation in several materials, namely, lead, copper, iron steel, and aluminum, are investigated under diverse exposure parameters to measure their ability to attenuate incident X-ray and their capability to reduce backscattered X-ray. Lead and iron steel shields exhibit the best abilities in attenuating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…This is because grid's material (iron and/or steel) which has better capability in attenuating of backscattered radiation. This result is in agreement with Naji et al (2016) who reported that the iron steel grid has best value in reducing backscattered radiation during X-ray examinations…”
Section: Image Contrast Variation At Various Massupporting
confidence: 83%
See 2 more Smart Citations
“…This is because grid's material (iron and/or steel) which has better capability in attenuating of backscattered radiation. This result is in agreement with Naji et al (2016) who reported that the iron steel grid has best value in reducing backscattered radiation during X-ray examinations…”
Section: Image Contrast Variation At Various Massupporting
confidence: 83%
“…Different antibackscattered grids show the best values in enhancement of image contrast index at lower peak tube voltage (50 kVp) because more backscattered photons can be attenuated by anti-backscattered grid by grid's base and strips. This result is in agreement with Naji et al (2016) who report that the best reduction of backscattered radiation can be obtained with lower exposure's energy.…”
Section: Image Contrast At Various X-ray Energy (Kvp)supporting
confidence: 82%
See 1 more Smart Citation
“…In case of the used filters, it should be considered that different materials have different attenuation properties depending on their atomic number and mass density 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…In case of the used filters, it should be considered that different materials have different attenuation properties depending on their atomic number and mass density 22,23 . Hence, Al (Z = 13) and Cu (Z = 29) show different attenuation patterns for X-ray photons also in dependence of their thickness and combination with each other 24 .…”
Section: Discussionmentioning
confidence: 99%